Investigating the Relationship between Neural Sensory Gateways and Creative Performance Using Convergent and Divergent Tasks. Issue 2 (2nd April 2020) - Ahsan, Naba; Van Benthem, Kathleen; Muldner, Kasia
ABSTRACT: The question of what type of attention is associated with creative potential has predominantly been examined using divergent thinking tasks and without the benefits of cognitive neuroscience methods. To address this gap, we rely on a neural approach by indexing attention using the P50 ERP component. The P50 measures sensory gating, which is the brain's ability to filter out or inhibit responses to repeated stimuli. We analyze the relationships between neural responses to P50 and performance on two tasks designed to measure creative potential: a convergent task and a divergent task. While we did not find evidence of a relationship between attention and the originality component of divergent thinking, our results show that leaky attention was positively associated with the fluency component of divergent thinking but negatively associated with performance on the convergent thinking task. This result highlights that the relationship between attention and performance on creative tasks may depend on the type of task.